Generation of Paramoeba perurans clonal cultures using flow cytometry and confirmation of virulence. Issue 3 (15th August 2016) - Collins, C; Hall, M; Bruno, D; Sokolowska, J; Duncan, L; Yuecel, R; McCarthy, U; Fordyce, M J; Pert, C C; McIntosh, R; MacKay, Z
Abstract: Amoebic gill disease (AGD) in farmed Atlantic salmon is caused by the amoeba Paramoeba perurans . The recent establishment of in vitro culture techniques for P. perurans has provided a valuable tool for studying the parasite in detail. In this study, flow cytometry was used to generate clonal cultures from single‐sorted amoeba, and these were used to successfully establish AGD in experimental Atlantic salmon. The clonal cultures displayed differences in virulence, based on gill scores. The P. perurans load on gills, determined by qPCR analysis, showed a positive relationship with gill score, and with clonal virulence, indicating that the ability of amoebae to proliferate and/or remain attached on gills may play a role in virulence. Gill scores based on gross signs and histopathological analysis were in agreement. No association between level of gill score and specific gill arch was observed. It was found that for fish with lower gill scores based on histopathological examination, gross examination and qPCR analysis of gills from the same fish were less successful in detecting lesions and amoebae, respectively.